Issues of Iraqi Photojournalists Working in Local and Foreign Institutions in Iraq: Iraqi Photojournalists Association - Case Study 2012 - Abbas Fadhil, Ali (ALBAHITH ALALAMI, 2012)
The issues of journalists and media employees in general and photojournalists in particular have become important issues, especially as those issues are closely linked to the success or failure of the media process. This research deals with (the issues of Iraqi photojournalists working in local and foreign institutions in Iraq - a case study in 2012), because of the ambiguity in identifying those issues, which focused on the issues of this research. This was done through the research community of members of the Association of Iraqi photojournalists in Baghdad exclusively of (64) photographers and television photographers to identify the problems encountered in their work in the local and foreign media; and the relationship of those problems with their professional performance; and what the relationship between photographers and existing bodies, whether negative or positive; and how far this relationship affects their performance. These questions were part of the research that the researcher sought to find scientific answers for them. A preliminary questionnaire was distributed to (10 %) of photographers from the research community containing open questions about the issues facing them. After retrieval, a final questionnaire was prepared based on the answers obtained. This form was presented to a group of arbitrators to certify the truth. The ratio was sufficient to complete the research. Then, the form was distributed to the respondents when it was retrieved and unloaded in tables. Finally, the results were interpreted to interpret the results. The researcher has reached a set of results, the most important of which are: • Half of the respondents confirmed that they (always) face an issue (not being involved in development courses), which has a negative impact on their work. • More than half of the respondents confirmed that they (always) suffer from the administrative issue of (imposing the institution’s policy on them). • Most of the respondents asserted that they are always faced with the problem (mistreatment by security forces at the scene). • The answers of the respondents confirmed that they were (always) looked at by (what the gunmen regard the photographers as spies). • Respondents confirmed that they (always) are (neglected or away from their family and social duties).